Bone marrow stem cell treatment in heart failure patients - Yu. I. Buziashvili; S. T. Matskeplishvili; D. Kh. Kamardinov; M. B. Usherzon; M. R. Grigoryan; L. A. Bokeriya (Кардиоваскулярная терапия и профилактика, 2005)
Chronic heart failure (CHF) treatment is an important problem of modern cardiology, with only one radical, but not universally possible solution – heart transplantation. Regenerative myocardial therapy, stem cell transplantation, raises increasing interest recently, due to many researchers’ doubts on genetic therapy for coronary heart disease and CHF management.